Clinical predictors of in‐hospital mortality in venoarterial extracorporeal membrane oxygenation. Issue 10 (13th August 2020) - Vigneshwar, Navin G.; Kohtz, Patrick D.; Lucas, Mark T.; Bronsert, Michael; J. Weyant, Michael; F. Masood, Muhammad; Itoh, Akinobu; Rove, Jessica Y.; Reece, Thomas B.; Cleveland, Joseph C.; Pal, Jay D.; Fullerton, David A.; et al.
Abstract: Introduction: Venoarterial extracorporeal membrane oxygenation (VA‐ECMO) is utilized as a life‐saving procedure and bridge to myocardial recovery for patients in refractory cardiogenic shock. Despite technical advancements, VA‐ECMO retains high mortality. This study aims to identify the clinical predictors of in‐hospital mortality after VA‐ECMO to improve risk stratification for this tenuous patient population. Methods: The REgistry for Cardiogenic Shock: Utility and Efficacy of Device Therapy database is a multicenter, observational registry of ECMO patients. From 2013 to 2018, 789 patients underwent VA‐ECMO. Bivariate analysis was performed on more than 300 variables regarding their association with in‐hospital mortality. Logistic regression analyses were performed with variables chosen based upon clinical and statistical significance in the bivariate analysis. Tests were considered significant at a two‐sided P < .05. Results: Although 63.5% patients were successfully weaned from VA‐ECMO, in‐hospital mortality was 57.9%. Nonsurvivors were older ( P < .0001), had higher body mass index ( P = .01), higher rates of hypertension ( P = .02), coronary artery disease ( P = .02), chronic obstructive pulmonary disease ( P = .02), chronic liver disease ( P = .008), percutaneous coronary intervention ( P = .02), and surgical revascularization ( P = .02). Multivariate predictors for in‐hospital mortality include older age (odds ratio [OR], 1.019; P = .007), cardiac arrest (OR, 2.76; P = .006), chronic liver disease (OR, 8.87; P = .04), elevated total bilirubin (OR, 1.093; P < .0001), and the presence of a left ventricular vent (OR, 2.018; P = .03). Pre‐ECMO sinus rhythm was protective (OR, 0.374; P = .006). Conclusions: In a large study of recent VA‐ECMO patients, in‐hospital mortality remains significant, but acceptable given the severe pathology manifested in this population. Identification of pre‐ECMO predictors of mortality helps stratify high‐risk patients when deciding on ECMO placement, prolonged support, and prognosis.